VOLCANIC TRIGGERING OF LATE PLIOCENE GLACIATION: EVIDENCE FROM THE FLUX OF VOLCANIC GLASS AND ICE-RAFTED DEBRIS TO THE NORTH PACIFIC OCEAN - Prueher L.M.; Rea D.K. (My University, 2001)
Mass accumulation rates (MAR) of different components of North Pacific deep-sea sediment provide detailed information about the timing of the onset of major Northern Hemisphere glaciation that occurred at 2.65Ma. An increase in explosive volcanism in the Kamchatka-Kurile and Aleutian arcs occurred at this same time, suggesting a link between volcanism and glaciation. Sediments recovered by piston-coring techniques during ODP Leg 145 provide a unique opportunity to undertake a detailed test of this possibility. Here we use volcanic glass as a proxy for explosive volcanism and ice-rafted debris (IRD) as a proxy for glaciation. The MAR of both glass and IRD increase markedly at 2.65Ma. Further, the flux of the volcanic glass increased just prior to the flux of ice-rafted material, suggesting that the cooling resulting from explosive volcanic eruptions may have been the ultimate trigger for the mid-Pliocene glacial intensification.
Keywords: PALEOCLIMATE; PLIOCENE; CLIMATE CHANGE; VOLCANISM; NORTH PACIFIC; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен